A case study of representational scenic designs of a theater group as an auxiliary form of interior design - Teodoro, Mikayla Therese R.
The study focused on the design processes of interior designers and representational scenic designers of a theater group according to the ADDIE model. The purpose of this study was to understand the similarities and differences of the two professions in order to render representational scenic design as an auxiliary form of interior design. The respondents were chosen through homogenous purposive sampling. Three (3) representational scenic designers from a theater performing group were chosen based on the fact that they had to have had designed a representational set in the last ten (10) years with the company while three (3) interior designers were also chosen to take part in the study. The interior designers had to have been practicing for at least five (5) years. The data gathering was done in the span of one (1) month. A descriptive case study was utilized and the data gathering instruments included a closed survey, a semi-structured face-to-face interview, and observations of photos of the chosen representational scenic designs given by the corresponding scenic designers. The analysis of data was done qualitatively as well as quantitatively in order to see frequencies in answers. Trends and similarities in comments were noted and looked for in the course of the study. Based on the findings, many similarities and differences were noticed from the two professions. Despite this, differences in typologies also arose due to the nature of both professions. Nevertheless, the similarities outweighed the differences rendering the design processes of interior design and representational design comparable in more ways than one. The researcher recommends that a greater field of study be done with more respondents in both interior design and representational scenic design.